Manajemen Pendidikan Karakter (Studi Multi Situs di SMP Negeri 2 dan SMP Negeri 1 Banjarmasin - Saparina, Ratna; Aslamiah, Aslamiah; Effendi, Rustam (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2024)
The aim of this research is a description of the character education development strategy at the selected sites which, among other things, has an influence on the indicators used, including the management strategy used, the process of empowering human resources (teachers), the existence of partnership participation, and the evaluation process of implementing programs. character building. This research uses a descriptive qualitative method which shows the results of the social situation in a comprehensive and in-depth manner based on analysis carried out by means of in-depth interviews with the sources used. The results of the research show that between the two sites (1) the strategy used in the character education process is preparation before implementing KBM and habituation to character education, (2) there are regular activities carried out to support the skills and professionalism of human resources (teachers), (3) Active collaborative participation among the school community (committee, parents/guardians, related agencies, and local residents), and (4) Periodic evaluation activities as material for improvement and development for the future regarding character education habits. Among the cross-site findings, there are differences between the two sites, namely (1) In site I, cooperative participation has not been carried out in a unified manner, in contrast to site II, there is awareness among related parties to advance the quality of character education, (2) other differences are in the determination of the parties involved. In the character education habituation process, site I empowers appropriate and competent parties to be involved in character education, unlike site II, there is implementation first followed by an evaluation, so that the results of the evaluation lead to decisions on the sustainability of the human resources (teachers) who carry out the education habituation. character, (3) the success of character education which is used by the parties (teachers) in site I, there is still a gap in self-awareness to develop themselves following training, and in site II there is a sense of interest in each teacher to participate in self-development.